Sistem penempahan bilik/ dewan/ makmal elektronik bagi Fakulti Sains Komputer dan Teknologi Maklumat / Hasan Ismail - Hasan, Ismail (2002)
Now day's On-line Reservations Service (ORS) are more easy and advance. But only some of this system has been developed to help people to do their reservations. In this millennium where people more often using the computers, it is the best time for developing this system by using all the technologies that related with the computer. By using these technologies, ORS will be easier to develop. Tempahan On-line Fakulti Sains Komputer Dan Teknologi Maklumat (To FSKTM) is one of the systems that developed to help administration and academic staffs to make their reservations and getting related information on-line by just visiting this system. This will help them doing reservation more easily and efficiency. Doing the usual manual reservation is not practical because of its lack. To FSKTM was designed to help faculty to managed reservations system and the related information in the systematic procedure. This will help to reduce any mistake that happen by using manual procedure. The overall design of the system is based on the concept of user-friendliness in order to allow users use the system in an easier way.